Application mediated communication: Panoptic surveillance in online transportation - Sulistyowati, Evit Dwi (Bricolage : Jurnal Magister Ilmu Komunikasi, 2023)
This study aims to reveal conditions that have been neglected so far regarding the development of communication technology in online transportation. With a large number of partners, the company provides features to service users to provide an assessment of online motorcycle taxi drivers. Companies are no longer present to discipline their workers with strict regulations, but by using a panopticon monitoring system that is delegated to service users. This study uses a qualitative approach by conducting surveys and interviews with online motorcycle taxi drivers and users. The results of the participant interviews were then analyzed and supported by documentation studies originating from books, journals, and some data obtained from online media, or also known as data triangulation. The results of the study show that the panopticon system implemented by the company provides certainty of supervision so that it forms the discipline of those who are supervised by forming homogeneous behavior. The power relations that occur between companies and their partners place online motorcycle taxi drivers in a vulnerable position to symbolic violence through supervision.